Aprendizaje basado en problemas: consideraciones para los graduados en medicina familiar y comunitaria en Ecuador. - Fernández Lora, Lilian; Montoya, Sucimil Fonseca (MEDISAN, 2016)
The learning based on problems is one in the ways of organization of teaching in the higher education which objective is guided to update the teaching staff who incorporate to the training process of the posgraduate education in family and community medicine, with a brief characterization of it, what is important for the planning, organization and implementation of the methodological and educational work in this teaching level. It is a mean for the students to acquire knowledge and use it to solve a real or simulated problem, without the masterful lesson of the teachers or another method to transmit the topics. Its implementation is as a didactic system based on the regularities of the creative appropriation of knowledge and an activity form which integrates teaching and learning methods, which are characterized to present basic features of the scientific search.